Evaluation of state measures applied in regulation of individual enterprise - Žukovskis, Janas (Ekonomika, 1999)
The main idea of this research is to evaluate relations between state and individual enterprise and to find the best solutions and decisions for goals and ways of state influence to the private propery. If we analyse problems today we will be able to forecast situation and consequences for society in future. The object of research - state measures applied in regulation of individual enterprise (IE) work. The aim of research - to evaluale the system of state measures applied in regulation of IE work. The goals of research: 1. To review the reasons of occurrence of stale measures applied in regulation of IE work in theoretical and historical contexts. 2. To describe IE as the subject whose work is useful 10 society. 3. To make the conception of regulation and state regulation more exact with respect to IE work. 4. To analyse the extent and character of state measures applied in regulation of IE work. 5. To work out the structure of the model of state measures applied in regulation of IE work. Research methods. Methods used in this work include analysis of scientific and periodical literature, of business regulating laws, of statistical scenarios and data, interview, questionnaires and other methods. It has been proved, that density of enterprises (number of enterprises taken to a certain number of populations) has direct influence on the size and formation of gross national product (GNP). So with the aim of increasing GNP and the number of work places it is necessary to create favourable conditions for establishment and work of IE. The system of state measures applied in regulation of IE work includes: regulation aims and goals, regulation object and subjects, regulation measures and methods, control mechanism. The state can have the following aims to increase gross national product (GNP), to decrease business risk, to create legal environment for protecting property and results of work, to induce competitition, to solve social problems (employment, nature protection, ecology, assunance of minimal income etc.), to stimulate export and work. From the point of view of the subject, the most important thing is how state regulation measures help to achieve his/her aims (to profit, to manage business, to use his/her own property, to dispose of the results of his/her work, to meet his/her obligations to the state and society, to profit by being in society, obeying to state compulsion). Basic state regulation measures must be tax system, the system of normative acts (obligations and rights), investment and credits policy, control of enterprise work and presentation of information. Generalising the elements of the structure of state measures model, it is necessary to emphasise the main idea: a state is founded for fulfilling certain tasks and functions, but not for solving all problems of society existence. All regulation measures must conform to this vision of state foundation. Therefore, in my opinion, cooperation principles are the most suitable characterising future relations of IE and state.